Determination Of The Mercury Content Of Lichens and Comparison To Atmospheric Mercury Levels In The South African Highveld Region - A. Trüe; N. Panichev; J. Okonkwo; P.B.C. Forbes (Clean Air Journal, 2012)
The concentration of mercury vapour in ambient air is routinely determined using specialised instruments. As an economical alternative, actively pumped Hopcalite sorbent tubes can be used to trap atmospheric mercury, which is subsequently analysed by cold vapour atomic absorption spectroscopy. Plant materials are also readily available in most regions and can be analysed to obtain information on time averaged atmospheric mercury levels. Lichen and tree bark samples were collected in the cities of Pretoria and Witbank, dried and acid digested with subsequent cold vapour atomic absorption spectroscopy. Average mercury concentrations ranging from 74 to 193 μg.kg-1 were found in lichens from three Pretoria suburbs, whilst average Hg levels of 228 μg.kg-1 were determined in lichens collected in Witbank. The average mercury concentration in tree bark was consistently lower than in lichens, with concentrations between 28 and 72 μg.kg-1 determined in samples from three Pretoria suburbs and 75 μg.kg-1 determined in samples taken in Witbank. This study is the first in South Africa to determine mercury levels in lichens and tree bark. Average total gaseous mercury concentrations in ambient air at the three Pretoria suburban sites, as determined by a semi-continuous spectroscopic method using Hopcalite sampling, ranged between 1.6 and 2.5 ng.m-3, while an average of 1.7 ng.m-3 was measured in Witbank over the sampling interval.